2016
DOI: 10.1249/mss.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise Augments Postprandial Overnight Muscle Protein Synthesis Rates

Abstract: Resistance-type exercise performed in the evening augments the overnight muscle protein synthetic response to presleep protein ingestion and allows more of the ingested protein-derived amino acids to be used for de novo myofibrillar protein synthesis during overnight sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 27 publications
5
68
0
Order By: Relevance
“…In the present study, we provided a bolus of 20 g of intrinsically labelled milk protein (together with 45 g of carbohydrates) after resistance-type exercise. In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation ( Fig. 4), thereby providing precursors for de novo myofibrillar protein synthesis (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we provided a bolus of 20 g of intrinsically labelled milk protein (together with 45 g of carbohydrates) after resistance-type exercise. In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation ( Fig. 4), thereby providing precursors for de novo myofibrillar protein synthesis (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation (Fig. In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted, however, that most postprandial plasma amino acid parameters (with the exception of total essential amino acids) and insulin levels were numerically higher when compared with the 60 g mycoprotein condition, and remained consistently elevated for the entire 4 h postprandial period (selected as a typical 'real world' postprandial period before subsequent meal consumption) in the 80 g mycoprotein condition only. This may be of relevance when considering postprandial periods expected to extend beyond 4 h. For example, pre-sleep protein is an increasingly popular strategy for augmenting muscle protein synthesis rates during the extended overnight period (52)(53)(54)(55)(56) , an approach also shown to augment the adaptive response to prolonged training (57) . Likely as a consequence of this extended overnight postprandial period, these studies have suggested that 'slower proteins' capable of facilitating more prolonged hyperaminoacidaemia, and in relatively larger doses, may be optimal for the stimulation of muscle protein synthesis rates.…”
Section: Discussionmentioning
confidence: 99%